Types of Questions Asked by Teachers at Primary School 077786 Tuhembaruzo in Classroom Interaction - Denar Yosafad Simatupang (Manunggal Halim Jaya, 2024)
This study aims to analyze the types of teacher questions in the teaching and learning process in three study groups and to analyze student activeness in the learning process at SD Negeri 077786 Tuhembaruzo. To obtain the results of this research, a descriptive qualitative method was used because this research focuses on phenomena that occur in the classroom. After analyzing it was found that there were 3 types of questions used by teachers in the study groups, namely procedural, convergent and divergent types of questions. the type of teacher questions in the three study groups at SD Negeri 077786 Tuhembaruzo was more convergent type than divergent and procedural types, namely 57, 23% of questions. While the teacher's procedural type questions amounted to 19.07% and the divergent type amounted to 23.68%.